Diversity Of Microchiropteran In Rubber Plot Of Kampung Sebayor And Peat Swamp Area In Universiti Malaysia Sarawak Campus And Morphometric Analysis Of Hipposideridae - Nor Hanisah, Binti Mad Halid (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The brief study on diversity of microchiroptera was carried out at UNIMAS campus from 14 August 2010 to 10 December 2010. This study was conducted at two sites; rubber plot of Kampung Sebayor (site A) and peat swamp area in UNIMAS east campus (site B). A total of fourteen individuals from nine species were captured using five harp traps and ten mist nets. Kerivoula hardwickii and Tylonycteris robustula were the most frequently captured from both areas. A preliminary investigation on the morphometric variation also done to show relationship between 25 individuals from five species within the same family which were Hipposideros larvatus, H. bic%r, H. cervinus, H. galeritus and H. diadema. A total of 22 characters comprised of external, cranial and dental measurements used to discriminate each species respectively. This study showed the species had clear separation in the Canonical Discriminant Analysis (CDA) and based on Discriminant Function Analysis (DFA), forearm and canine molar length (CIM3L) have higher character loading where these characters can be used as diagnostic character in distinguishing the species.